Mouth preparation dengan pendekatan farmakologis pada anak penderita ventricular septal defect - Niniek S. Salurapa; Sri Ramadany (DiscoverSys Inc., 2009)
Congenital heart defect is a form of cardiovascular disease present since birth andoccurs due to development disorder. A type of congenital heart defect is ventricularseptal defect. Oral sedation has been used in dentistry, especially on child patients toovercome the anxiety of dental care. Chloral hydrate is a monohydrate derivate fromchloral (trichloroacetaldehyde)which is hypnotic sedative medication and which isused for oral sedation. Chloral hydrate is used to mitigate anxiety before operation,usually after operation to overcome pain. Management of cardiovascular childpatients in dentistry requires complete handling, in efforts to prevent the occurrenceof bacterialis endocarditis. This paper discusses oral and dental condition and theirmanagement in cases of children with ventricular septal defect heart disorder. A sixyearold boy was reported with ventricular septal defect going to undergo a heartoperation. The patient was very non-cooperative in getting dental treatment. Oralsedation with chloral hydrate was performed for patient during dental patching andextracting. Mouth preparation was completed in two visits.